TINJAUAN EVOLUSI LOGO BATMAN DALAM FILM TAHUN 1966 HINGGA TAHUN 2005 - Sayid Mataram (Canthing, 2012)
Just as the name, logo needed to identify a product. No exception to the fantasycharacter Batman is more a product of the DC Comic. Logo not merely as a badge of identity such figures, but also contains an implied meaning so as to guide the emotions of the audience to enjoy the scene and the role of such figures as part of the composition of the comics, animation, television series or movie theaters.Keywords: Logo, Evolution, Batman, Comic, Movie